Overlapping Signs and Symptoms Between Recurrent Varicella and Pityriasis rosea Gibert. Issue 9 (24th June 2022) - Baba, Koichi; Baba, Tomoko; Ogra, Pearay L.; Okuno, Toshiomi
Abstract : Background: Pityriasis rosea Gibert (PRG) has features similar to those of common infectious childhood diseases, suggesting a viral cause, but no agent has been identified to date. We describe 4 children with PRG and 2 with recurrent varicella who were studied using photochronography, virology and immunology. Methods: The 6 patients with skin rashes visited our pediatric clinic from April 2012 to May 2016. Photographs of their skin lesions were taken; blood, skin lesions, and/or nasal lavage samples were collected to detect varicella-zoster virus (VZV) DNA and antibodies; and skin tests were carried out to measure cell-mediated immunity to VZV. Results: Herald patches were confirmed in 2 of 4 PRG patients. No specimen cultures were positive for infectious VZV. However, VZV-DNA was detected in skin lesions of 3 PRG patients. During the acute phase, 5 patients had IgG antibodies to VZV, and skin-test reactions were positive in 5 patients. Conclusions: IgG antibody titers to VZV at rash onset were high, suggesting that they were already rising at the appearance of the rash and that reinfection with VZV must have occurred during the prodromal stage or several weeks before rash appearance in PRG patients whose immunity had declined below the threshold. Our study suggests a new pathogenesis of PRG that might help to address incongruities of past theories on PRG sites of viral entry and replication, incubation period and variations in the clinical course of PRG from prodrome to healing.